2016
DOI: 10.1021/jacs.6b00179
|View full text |Cite
|
Sign up to set email alerts
|

The Ligand Shell as an Energy Barrier in Surface Reactions on Transition Metal Nanoparticles

Abstract: Transition metal nanoparticles, including those employed in catalytic, electrocatalytic, and photocatalytic conversions, have surfaces that are typically coated with a layer of short or long-chain ligands. There is little systematic understanding of how much this ligand layer affects the reactivity of the underlying surface. We show for Ag nanoparticles that a surface-adsorbed thiol layer greatly impedes the kinetics of an ionic chemical reaction taking place on the Ag surface. The model reaction studied is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
69
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 58 publications
4
69
0
Order By: Relevance
“…[21] This is consistentw ith ap revious observation, where as hort thiolate ligand length would form at hin protecting layer around the gold core, whereas al onger thiolate ligand might be self-organized into bundles owing to the strong hydrophobic interaction between theh ydrophobic alkyl chain, thus increasing the packing density of the ligand shell that could create at hicker barrierw ith more steric hindrancea nd highere nergy barrier for the diffusion of the reactants. [13,35] This could readily explain the catalytic trend observed in the presents tudy.I np articular,a ni ncreasei nt he ligand chain length would provide ah igher density barrier for the reactants to diffuse inside the ligand shell to approacht he goldc ore of Au 25 (SR) 18 NCs, leading to al ongeri nductionp eriod and al ower catalytic activity.…”
supporting
confidence: 66%
See 2 more Smart Citations
“…[21] This is consistentw ith ap revious observation, where as hort thiolate ligand length would form at hin protecting layer around the gold core, whereas al onger thiolate ligand might be self-organized into bundles owing to the strong hydrophobic interaction between theh ydrophobic alkyl chain, thus increasing the packing density of the ligand shell that could create at hicker barrierw ith more steric hindrancea nd highere nergy barrier for the diffusion of the reactants. [13,35] This could readily explain the catalytic trend observed in the presents tudy.I np articular,a ni ncreasei nt he ligand chain length would provide ah igher density barrier for the reactants to diffuse inside the ligand shell to approacht he goldc ore of Au 25 (SR) 18 NCs, leading to al ongeri nductionp eriod and al ower catalytic activity.…”
supporting
confidence: 66%
“…For example, several studies suggested negative effects of ligands on the catalytica ctivity of Au NCsb ecause the ligand shell on the NC surfacec ould createaphysicalb arrier,w hich would hindert he diffusion of substrates to the catalytic actives ites. [1,13,[27][28][29] On the other hand,s ome studies also highlighted positivee ffects of the ligandso nt he catalytic performance of Au NCs. [30,31] For example, Katz et al demonstratedt hat different-sized calixarene ligandsc ould be used to facilitate the accessibility of substrates towardst he metal core of Au NCs.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Access of molecular substrates to the inorganic surface of the QD is necessary for applications in photo-redox catalysis, in order to provide sufficient electronic coupling for electron and hole extraction, [15][16][17] so water-solubilization strategies that involve replacing the hydrophobic shell of the QD with as ilica shell or encapsulatingt he hydrophobic QD in an amphiphilic polymer are not suited for QD-basedc atalysis. [18,19] Exchange of native hydrophobicligandsfor very polar or charged ligands is av ersatile strategy for creatingw ater-solublep articles, since not only the chemicals tructure but also the density of ligands can be controlled. In addition to providing access to the QD surface and, ideally,e ncouraging catalytic substrates to adsorb in activated geometries,s uch ligandsn eed to make the particles colloidally stable in water for the lifetimeo ft he illumination (or longer)b yi nhibiting agglomeration,w hichd ecreases catalytically actives urfacea rea and eventually leads to precipitation.T he most basic requirement for preventing agglomeration is that ligands mustn ot desorbf rom the QD surface at the catalytically relevant pH, ionic strength,a nd reagent/product concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, protective agents, such as polymers, ligands, and surfactants, are usually required during preparation to obtain stable monodisperse nanocrystals with specific morphologies and structures. For better or worse, protective agents adsorbed on the surface of nanocrystals will extremely affect the catalytic property of the nanocatalyst . Consequently, research on the effect of protective agents upon the catalytic property of nanocrystals is significant for understanding the intrinsic reaction behaviors of reactant molecules over nanocrystal catalysts, and helpful for further design and application of highly efficient catalysts prepared with various nanocrystals as building blocks.…”
Section: Introductionmentioning
confidence: 99%